Transcriptome analysis of genes involved in flower and leaf color of Oncidium by RNA-seq - Ma-Yin Wang; Yu Ding; Ye Zhang; Lu Sun; Xi-Qiang Song; Dai-Cheng Hao; Wei-Shi Li; Min-Qiang Tang; Peng Ling; Shang-Qian Xie (Acta Scientiarum Polonorum: Hortorum Cultus, 2023)
Oncidium, an important tropical orchid, has high ornamental value due to its specific color and occupies a significant market position for the worldwide flower. Transcriptome analysis of flower and leaf color formation provides new sources for producing novel Oncidium hybridum cultivars. We sequenced 12 samples of flowers (yellow and white) and leaves (striped and regular) of O. hybridum and assembled 381,136 and 453,566 unigene sequences from RNA-seq data, respectively. Among unigenes, 662 and 1,324 differentially expressed genes were identified in flower and leaf samples, respectively. Gene ontology and pathway enrichment showed that secondary metabolite biosynthetic pathways were responsible for flower and leaf color formation. It was determined that UGT75C1, E2.4.1.115, CCD7, E2.1.1.76, and CCoAOMT are involved in regulating flower color, and UGT75C1, LHCB, UGT, RP-L18Ae, and ABCB1 play crucial roles in regulating leaf color. Kyoto Encyclopedia of Genes and Genomes analysis revealed that UGT75C1 was significantly enriched in the anthocyanin biosynthetic pathway, showing effects on flower and leaf colors. This study was the first detailed analysis of the molecular mechanisms of O. hybridum flower and leaf colors, and the results advanced the understanding of the genetic basis of flower and leaf colors; they also provided additional support for improving commercial value and producing novel cultivars of O. hybridum.